Pacientes com DPOC frágeis e pré-frágeis: investigação da função respiratória, atividades de vida diária, capacidade funcional e qualidade de vida - Paschoini, Bruna Camila (2018)
Introduction: Patients with chronic obstructive pulmonary disease (COPD) present high fragility prevalence compared to healthy patients. However, little is known about the fragility in COPD patients related to functional capacity during daily tasks. Objectives: Evaluate and compare the variables in spirometric, the cardiorespiratory during DLT, predictors of severity, ability to the exercise, corporal composition, muscular respiratory strength, thoracoabdominal mobility and life quality among pre-fragile and fragile COPD patients. Methods: Cross sectional study, comparative with sampling by convenience. 24 patients were evaluated with clinical and spirometric diagnosis of COPD, divided into two groups: pre-fragile COPD group (PF-COPDG) and fragile COPD group (F-COPDG), from the fragility phenotype evaluation. The patients were submitted to anamnesis, spirometry, corporal composition evaluation, thoracoabdominal mobility and to the DLT tests. Furthermore, they answered the dyspnea scales and life quality, then the BODE index were calculated. The DLT test was performed with and without the ECT (Energy Conservation Techniques) use in an adapted laboratory with an interval of at least one week, and the activities were randomized by lottery. Results: The F-COPDG presented lower values of PEF (p=0.02), palmar prehension strength (p=0.02), weight loss not intentional (p=0.007) and abdominal amplitude index (p=0.02). The LCADL scale presented significantly higher scores in the total score (p=0.008) and in the CRQ lower scores than the total score (p=0.013) compared with the PF-COPDG. In the intergroup analysis: higher CF in the DLT-B without ECT, smaller sensation of dyspnea in the DLT-B with ECT, dyspnea and muscular weariness in the DLT-Mant_ASG with and without ECT, larger dyspnea sensation in the DLT-Mant_BPG with ECT. In the intragroup analysis: higher dyspnea sensation in the DLT-CC was performed without ECT, lower task execution time DLT-B, DLT-CC and DLT-EC. Conclusion: Patients with fragile COPD presented lower permeability of the airways, muscular strength in the superior limb, larger abdominal mobility, higher execution time and dyspnea and weariness sensation when performing the DLT, and worst life quality when compared to the pre-fragile COPD patients.